HUBUNGAN CARA BELAJAR DAN DUKUNGAN KELUARGA DENGAN PRESTASI BELAJAR MATA KULIAH KEPERAWATAN KOMUNITAS - Triwibowo, Heri (JURNAL KEPERAWATAN BINA SEHAT, 2013)
Background :The problems facing the world today is the low educational achievement of students. Learning achievement is the main yardstick to determine the success of ones learning . Factors influencing learning achievement is a learning habitand family support.Objectives:Determine the correlation between learning habitand family support with a cademic achievement of Community nursingon 4thsemesters Student of Bina Sehat PPNI Nursing Academy Mojokerto.Methods :The study was an analytic observational with cross sectional design . Large population as many as 136 students, sampling technique using cluster random sampling and sample obtained as many as 101 respondents.The research instrument was a learning achievement test , observation sheets , and a Likert scale is valid and reliable . Data Analysis test using linear regression analysis with the prerequisite test : normality test, linearity test and multicollinearity test with significance level 0.05 level.Results : (1 ) There is a significant correlation between learning habit with academic achievement of Community nursingon 4thsemesters Student of Bina Sehat PPNI Nursing Academy Mojokerto ( ρ : 0.000 < α : 0,05 ) . ( 2 ) There is a significant correlation between family support with academic achievement of Community nursingon 4thsemesters Student of Bina Sehat PPNI Nursing Academy Mojokerto ( ρ : 0.000 < α : 0,05 ) . ( 3 ) There is a significant correlation between learning habitand family support with academic achievement of Community nursing on 4thsemesters Student of Bina Sehat PPNI Nursing Academy Mojokerto ( ρ : 0.000 < α : 0,05 )Conclusion :There is a significant correlation between learning habitand family support with academic achievement of Community nursingon 4thsemesters Student of Bina Sehat PPNI Nursing Academy Mojokerto. Where, the effective contribution learn more dominant way contribute to the achievement of nursing science courses compared to community family supportKeywords :Learning habit, Family Support , academic achievement of Community nursing.